Antibacterial Activity of Actinomycetes Isolated from Foothill Soils of Shivalik Range, Dehra Dun (Uttarakhand) - Mathpal, Vaishali; Bisht, Gajraj Singh (Indian Forester, 2007)
Some actinomycetes were isolated from four different localities of Dehradun i.e. Forest Research Institute, Balawala village, Dharampur and Rajpur village. Thirty isolates were selected for testing antibacterial activity, out of which only 16 isolates were found to be positive in primary screening against 5 test organisms i.e. Pseudomonas aeruginosa, Bacillus cereus, Staphylococcus aureus, Salmonella typhi and Escheria coli which were subjected to the secondary screening in shake flask culture in which 2 isolates were active against Staphylococcus aureus. Out of 30 isolates 26 were tentatively identified as Actinomadura livida, Chainia rubera, Dematophillus sp., Nocardia sulphuva, Streptomyces anthocyanicus, S. armeniacus, S. bobili, S. californicus, S. chromofuseus, S. clavifer, S. clavuligerus, S. ederensis, S. floridae, S. gobitricini, S. griseoloalbus, S. Kumingenesis, S. longisporoflavus, S. noboritoensis, S. noursei, S. peucetius, S. pulveraceus, S. somaliensis, S. torulosus, S. violaceochromogenes, Streptosporangium sp. and Streptoveticillium sp.